EFECTO EN LA EMERGENCIA, CRECIMIENTO Y PRODUCCIÓN DEL CHILE CAYENNE LONG SLIM (Capsicum annuum L.) CON LA BIOFERTILIZACIÓN DEL ALGA MARINA (Ascophyllum nodosum) - Martínez Zamora, Fabián Vicente (2023)
The present research project aimed to assess the effects of applying biofertilization based on the seaweed Ascophyllum nodosum on the emergence, growth, and production of Cayenne Long Slim Chili (Capsicum annuum L.). A completely randomized design with four treatments and a control, each with four replications, was employed. The concentrations of the A. nodosum seaweed used were T0-0%, T1-100%, T2-75%, T3-50%, and T4-25%. Two trials were conducted: the first focused on the emergent phase, with variables including emergence percentage, plant height, leaf length and diameter, root length, and fresh and dry biomass. The control in this trial showed that during the initial stage of Cayenne Chili cultivation, the seaweed had an impact.